Analisis Self-efficacy Matematis Peserta Didik dalam Problem-based learning di SMPN 3 Sungai Tarab - Desri Rahmah Putri; Isra Nurmai Yenti; Dona Afriyani; Ali Umar (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Mathematical self-efficacy is essential for learning mathematics because students’ beliefs about their abilities influence how they approach problems, persist through difficulties, and interpret success and failure. This study aims to describe the effect of Problem-Based Learning (PBL) on the mathematical self-efficacy of eighth-grade students at SMPN 3 Sungai Tarab. The study employed a qualitative descriptive design, in which questionnaire percentages served as categorical descriptors rather than a basis for statistical hypothesis testing. Eighteen students were purposively selected after completing one semester of PBL. Data were collected through methodological and source triangulation using a mathematical self-efficacy questionnaire (Cronbach’s alpha = 0.924), participatory observation, and in-depth interviews. Students’ mathematical self-efficacy in the PBL setting was categorized as high, with average percentages of 69.3% from the questionnaire and 64.1% from the observations. PBL most strongly developed dimensions closely related to its learning activities, namely positive and constructive attitudes (71%) and emotional stability (71%), fostered through collaborative problem-solving and viewing mistakes as part of learning, followed by applicative ability (68%). The lowest score was found in inherent motivation (67%), indicating that while PBL effectively strengthened students’ confidence in completing classroom tasks, it had not fully promoted self-directed learning beyond the classroom. Overall, the findings suggest that PBL effectively enhances mathematical self-efficacy at the task level, while self-directed learning remains an area for further improvement. Collaborative learning, contextual problems, appropriate teacher guidance, and motivation were identified as key supporting factors.